Development of Honesty Attitude Assessment Instruments for Junior and Senior High School Students - Sinta, Dewi; Rahmat, Munawar; Anwar, Saepul (Universitas Muhammadiyah Mataram, 2024)
The preparation of honesty attitude assessment instruments is essential for planning to improve student honesty. Assessment and improvement of student honesty in the educational environment are critical to forming a strong character of integrity. This study aims to develop an honesty attitude assessment instrument for junior high and high school students. This study uses a development research method with a theory development model. The instrument's development was first conducted through a theoretical study with a literature study to formulate indicators. Then, the researcher created an instrument based on these indicators, consulted with the supervising lecturer, asked for expert judgment, conducted validity and reliability tests, and conducted analysis. The study results showed four indicators of honesty: honesty, trustworthiness, keeping promises, and fairness. The instrument developed was in the form of 40 questionnaire items using a Likert scale. This instrument was tested on 103 grade 9 students at SMP Laboratorium Percontohan UPI. The analysis showed that the instrument was valid and reliable, with an alpha coefficient of 0.8723. The practical implications of this study indicate that this instrument can be used in quasi-experimental research. Theoretically, this study can enrich the theory of measuring honesty attitudes and be the basis for further research.